The ribosome biogenesis factor Nol11 is required for optimal rDNA transcription and craniofacial development in Xenopus. - John N Griffin; Samuel B Sondalle; Florencia Del Viso; Susan J Baserga; Mustafa K Khokha (PLoS Genetics, 2015)
The production of ribosomes is ubiquitous and fundamental to life. As such, it is surprising that defects in ribosome biogenesis underlie a growing number of symptomatically distinct inherited disorders, collectively called ribosomopathies. We previously determined that the nucleolar protein, NOL11, is essential for optimal pre-rRNA transcription and processing in human tissue culture cells. However, the role of NOL11 in the development of a multicellular organism remains unknown. Here, we reveal a critical function for NOL11 in vertebrate ribosome biogenesis and craniofacial development. Nol11 is strongly expressed in the developing cranial neural crest (CNC) of both amphibians and mammals, and knockdown of Xenopus nol11 results in impaired pre-rRNA transcription and processing, increased apoptosis, and abnormal development of the craniofacial cartilages. Inhibition of p53 rescues this skeletal phenotype, but not the underlying ribosome biogenesis defect, demonstrating an evolutionarily conserved control mechanism through which ribosome-impaired craniofacial cells are removed. Excessive activation of this mechanism impairs craniofacial development. Together, our findings reveal a novel requirement for Nol11 in craniofacial development, present the first frog model of a ribosomopathy, and provide further insight into the clinically important relationship between specific ribosome biogenesis proteins and craniofacial cell survival.